4a-6+6=12+6-2a

Simple and best practice solution for 4a-6+6=12+6-2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-6+6=12+6-2a equation:



4a-6+6=12+6-2a
We move all terms to the left:
4a-6+6-(12+6-2a)=0
We add all the numbers together, and all the variables
4a-(-2a+18)-6+6=0
We add all the numbers together, and all the variables
4a-(-2a+18)=0
We get rid of parentheses
4a+2a-18=0
We add all the numbers together, and all the variables
6a-18=0
We move all terms containing a to the left, all other terms to the right
6a=18
a=18/6
a=3

See similar equations:

| -2(-3h-5)=34 | | 2x+6=10–30 | | 2(-7g+3)=-22 | | z+2+2z+5+z=63 | | 4x-5=3x-19 | | x+x+x+6+x+6=80 | | 2(8x-6)=20 | | 2(3t-5)=20 | | x+6+x+x+6+x=80 | | (7r-6)=(7r+6) | | n/14=4 | | m/8=18 | | n/17=8 | | 18=z/12 | | 2x/3+5/2=x/6 | | 11+2a=9-2a | | 11c+78=5c | | 3(2x+9)-20=4x | | 18m+-11m+-17m-10=10 | | 4(x-8=10 | | 1,6x+7=3,5x+3,2 | | -18-13s=15 | | 2x÷73=201 | | 12y−5=2y+15 | | 12y−5=3y+22 | | 20+x=35-2x | | 0.8(2x-6)=0.3x+0.9 | | 1y+3/0=1 | | 3x+2(x−9)= | | 9=10+-9v | | 3v−4=11 | | 3(m+9)=87 |

Equations solver categories